Diagnostic and Prognostic Performance of Neurofilaments in ALS - Poesen, Koen; Van Damme, Philip (Frontiers in Neurology, 2019)
There is a need for biomarkers for amyotrophic lateral sclerosis (ALS), to support the diagnosis of the disease, to predict disease progression and to track disease activity and treatment responses. Over the last decade multiple studies have investigated the potential of neurofilaments levels, both in cerebrospinal fluid and blood, as biomarker for ALS. The most widely studied neurofilaments subunits are neurofilaments light chain (NfL) and phosphorylated neurofilaments heavy chain (pNfH). Neurofilament levels are reflecting neuronal injury and therefore potentially of value in ALS and other neurological disorders. In this mini-review, we summarize and discuss the available evidence about neurofilaments as diagnostic and prognostic biomarker for human ALS.